Across the vanishing sky - Cowles, Catherine (Starlight Grove, 2026)
"Braedyn knows what it's like to have your life change in a single moment. Hers has three times. Once when she saw the two little lines on that pregnancy test at just twenty-one. Another when the father of her child said he wanted nothing to do with them. And again when her best friend disappeared without a trace. But Braedyn doesn't give up easily and when she hears that an infamous hacker has returned to Clover Creek, she's determined to enlist his help in finding her friend. The last place Dex wanted to return to was Clover Creek. But when he finds out his great uncle, the one person who didn't turn their back on him and his brothers, is sick, he doesn't have a choice. The last thing he needs is a reason to stay longer than necessary. But the moment Braedyn shows up on his doorstep, all his defenses falter. When he hears her desperate pleas to help her find her lost friend, he can't turn her away. And when he meets her precocious, charming daughter, he starts to wonder if he could have the family he always thought would be impossible for him. But dark forces are swirling around Clover Creek and when Dex and his brothers start digging into what is really happening in their small town, those forces will do anything to stop them"-- Provided by publisher.